Infobuttons for Genomic Medicine: Requirements and Barriers - Rasmussen, Luke V.; Connolly, John J.; Del Fiol, Guilherme; Freimuth, Robert R.; Pet, Douglas B.; Peterson, Josh F.; Shirts, Brian H.; Starren, Justin B.; Williams, Marc S.; Walton, Nephi; Taylor, Casey Overby (Applied Clinical Informatics, 2021)
Objectives The study aimed to understand potential barriers to the adoption of health information technology projects that are released as free and open source software (FOSS).Methods We conducted a survey of research consortia participants engaged in genomic medicine implementation to assess perceived institutional barriers to the adoption of three systems: ClinGen electronic health record (EHR) Toolkit, DocUBuild, and MyResults.org. The survey included eight barriers from the Consolidated Framework for Implementation Research (CFIR), with additional barriers identified from a qualitative analysis of open-ended responses.Results We analyzed responses from 24 research consortia participants from 18 institutions. In total, 14 categories of perceived barriers were evaluated, which were consistent with other observed barriers to FOSS adoption. The most frequent perceived barriers included lack of adaptability of the system, lack of institutional priority to implement, lack of trialability, lack of advantage of alternative systems, and complexity.Conclusion In addition to understanding potential barriers, we recommend some strategies to address them (where possible), including considerations for genomic medicine. Overall, FOSS developers need to ensure systems are easy to trial and implement and need to clearly articulate benefits of their systems, especially when alternatives exist. Institutional champions will remain a critical component to prioritizing genomic medicine projects.
Keywords: facilitators and barriers; clinical decision support; genetics; infobuttons; open source